2016
DOI: 10.1016/j.jhydrol.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

An overview of current applications, challenges, and future trends in distributed process-based models in hydrology

Abstract: 46Process-based hydrological models have a long history dating back to the 1960s. 47Criticized by some as over-parameterized, overly complex, and difficult to use, a more 48 nuanced view is that these tools are necessary in many situations and, in a certain class of 49 problems, they are the most appropriate type of hydrological model. This is especially the 50 case in situations where knowledge of flow paths or distributed state variables and/or 51 preservation of physical constraints is important. Examples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
339
0
5

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(345 citation statements)
references
References 264 publications
(9 reference statements)
1
339
0
5
Order By: Relevance
“…This approach was inspired by Weiler and McDonnell (2004), who suggested using numerical experiments to isolate hypotheses and investigate their influence on the model output. In a recent review paper, Fatichi et al (2016) acknowledge these studies to be different from the ones aiming at comparing performances of different models or validating model results. The word "synthetic" implies therefore that the focus is exclusively on how the different DRP maps influence the simulated runoff, and not on how well the model reproduces a measured discharge.…”
Section: Synthetic Runoff Simulationsmentioning
confidence: 99%
“…This approach was inspired by Weiler and McDonnell (2004), who suggested using numerical experiments to isolate hypotheses and investigate their influence on the model output. In a recent review paper, Fatichi et al (2016) acknowledge these studies to be different from the ones aiming at comparing performances of different models or validating model results. The word "synthetic" implies therefore that the focus is exclusively on how the different DRP maps influence the simulated runoff, and not on how well the model reproduces a measured discharge.…”
Section: Synthetic Runoff Simulationsmentioning
confidence: 99%
“…The above points do however not contest the immense value of physically based models as recently discussed in detail by Fatichi et al (2016). Rather, detailed implementations of these models, in spite of the associated limitations, have in the past been shown to be powerful tools to reproduce and understand spatially heterogeneous system-internal flux and state dynamics as well as patterns that emerge from the interaction of small-scale processes (e.g.…”
Section: Modelling Myths -Or Not?mentioning
confidence: 99%
“…. Fatichi et al (2016) argue that this suggests that uncertainties in observed system input and output data and the resulting biased parameters in calibrated models (e.g. Renard et al, 2010) outweigh uncertainties introduced by insufficient heterogeneity and/or an unsuitable scale.…”
Section: "Physically Based Models Have Too Many Degreesmentioning
confidence: 99%
See 1 more Smart Citation
“…Top-down models and parameterisations may be too simplistic and, therefore, require calibration (e.g. Fatichi et al, 2016), whereas physically-based models may be too data demanding and not 20 flexible enough to cope with emergent patterns at large scales (Beven, 2000).…”
Section: Introductionmentioning
confidence: 99%